PEMIKIRAN JOHN BURTON ATAS NASKH DALAM AL-QURAN DAN HADIS - Muhammad Asywar Saleh (Faculty of Ushuluddin UIN Syarif Hidayatullah Jakarta, 2019)
This paper informs the thoughts of a Western scholar, John Burton, related to his commentary on the naskh theory addressed to the Quran and Hadith or in other terms Tradition, borrowed the term Burton. In his book, al-Suyuthi quotes the words of the scholars that no one can interpret the Quran except after he knows the science of nāskh. Therefore, the concept of naskh is important to be studied further through the new perspective of scholars both Muslim and Non-Muslim. John Burton was selected to be studied because he was among the earliest Western scholar who shows great concern for the discussed matter in the field of the Quran and Hadith studies. From this writing, it was found, that in Burton’s view, the removal of the verse and its rules were ideas made by Muslim fuqaha who tried to base their legal decisions on the Quran even though the text of the Quran had no reference to that decision.